Investigation of Febrile Neutropenic Cases and Risk Factors - Ozden, Mehmet (Galenos Yayincilik, 2013)
Introduction: Febrile neutropenia is one of the most important factors responsible for morbidity and mortality in cancer patients. Materials and Methods: In this study, febrile neutropenic attacks seen in 100 patients who were consulted between January 2008 and December 2009 were retrospectively evaluated. Only the first attack of each patient was included in the study. Results: Fifty-eight of the patients were female and 42 were male. Mean age of the patients was 59.4 +/- 13.4 years. Primary malignancies were hematologic malignancy in 30 patients and solid tumors in 70 patients. According to the Multinational Association for Supportive Care in Cancer criteria, 29 of the patients were in the low-risk group, whereas 71 patients were in the high-risk group. Mean absolute neutrophil count, mean duration of the neutropenic period and mean duration of hospitalization were 247.8 +/- 25.2/mm(3), 3.3 +/- 1.9 days and 4.4 +/- 0.7 days, respectively. Of the 100 neutropenic attacks, 22 were clinically defined infection, 39 were microbiologically defined infection and 39 were fever of unknown origin. The most frequent infection sites were pneumonia and pyelonephritis based on the clinical and microbiological findings. Isolated strains included 44 gram-negative bacilli, four gram-positive cocci and nine Candida spp. Escherichia coli was the most frequently isolated agent in these strains. Empirical treatment of patients included monotherapy (61%) and combined therapy (39%). The most frequently used antimicrobial agents in monotherapy were cefoperazone-sulbactam. Mean fever defervescence time after initiation of empirical treatment was 2.6 +/- 0.2 days. Fifteen of the patients died during the febrile neutropenia attack. Conclusion: Clinical and microbiological approaches should be made carefully in order to determine the focus of infection in patients with febrile neutropenia. Early initiation of empiric antimicrobial treatment seems to be important in reducing mortality.
Keywords: Febrile neutropenia; cancer; risk factors